The role of aridification in constraining the elevation range of Holocene solifluction processes and associated landforms in the periglacial belt of the Sierra Nevada (southern Spain) - Oliva, Marc (2019)
Climate variability during the Mid-Late Holocene has influenced the activity of geomorphic processes in the current periglacial belt of the Sierra Nevada. We studied two types of sedimentary records that reveal a synchronous timing for slope instability in this high semi-arid massif: solifluction landforms and mountain lake sediments. Lithological and sedimentological properties of both records have recorded numerous cycles of different magnitude of slope processes in the massif. Solifluction deposits record seven phases of solifluction activity and soil development during the last 7 ka BP and lake sediments show evidence of eight periods with increased geomorphic activity in the catchments over the last 6 ka BP. Although present-day climate conditions do not promote active solifluction processes in the Sierra Nevada, colder and wetter periods during the Holocene triggered solifluction and transported coarse-grained sediments into the lakes. By contrast, warm phases favoured soil formation and spread an incipient vegetation cover over the headwaters of the highest valleys, diminishing the grain size of the particles reaching the lakes. Lake sediments record an aridification trend in the massif intensifying since 4·2 ka BP that has conditioned solifluction activity to shift gradually to higher elevations. During major cooler phases such as the Little Ice Age active solifluction was recorded back down to 2500 m altitude.